Upregulating Positive Affectivity in the Transdiagnostic Treatment of Emotional Disorders: A Randomized Pilot Study. Issue 1 (January 2019) - González-Robles, Alberto; García-Palacios, Azucena; Baños, Rosa; Quero, Soledad; Botella, Cristina
Transdiagnostic cognitive-behavioral therapy for emotional disorders (ED) has proven to be effective. However, current transdiagnostic treatment protocols address only the regulation of negative affectivity, and they do not include treatment components to more directly target the regulation of positive affectivity. In this study, we propose to evaluate the preliminary efficacy and acceptability of a transdiagnostic treatment protocol for ED that includes, as an innovative feature, a specific treatment component to directly upregulate positive affectivity based on positive psychology interventions. A total of 24 participants were randomized to either a transdiagnostic treatment protocol ( n = 12) or a transdiagnostic treatment protocol with an additional component designed to regulate positive affectivity ( n = 12). Participants completed measures of anxiety, depression, positive and negative affectivity, and quality of life, as well as treatment acceptability at pre- and posttreatment and at the 3-month follow-up. Both interventions led to improvements in all measures at posttreatment, and these outcomes were maintained at the 3-month follow-up, with large effect sizes for all measures. The effect sizes for positive affect were larger in the condition that included the component to upregulate positive affectivity. Attrition rate was low, and both treatment protocols were well accepted by participants. The results obtained in this study indicate the feasibility of testing the treatment protocol in a larger, randomized, controlled trial, and they suggest the potential of including treatment components for directly upregulating positive affectivity in future research on transdiagnostic treatment protocols for ED.